Congruent and incongruent self-concept of students in different types of communication - Tatiana S. Vershinina (Развитие образования, 2023)
The purpose of the article is to identify the influence of the stability of the self-concept and different types of communication on the communicative tactics of interpersonal interaction, represented in the speech act. The hypothesis states that incongruence/congruence of self-concept determines the choice of speech act of the person in the process of cognition; the type of self-concept system that affects relationships with people is reflected in the speech act. Speech act, according to the concept of contextual education, is a unit of communication, the basis of activity and social interaction. The article presents the results of empirical research, in which 333 first-year students of two universities of Yekaterinburg participated. J. Kelly's repertory grid technique was used in the study. Personality constructs, which are obtained in the study, are constructed on the basis of bipolar differences. Personal constructs allowed us to identify the type of communication that affects the relationship with people; they allow us to evaluate the self-concept of first-year university students; self-esteem, assessment of significant others, real self and ideal self-presented in the constructs give an idea of the stability of the self-concept and the presence of cognitive conflicts caused by personal characteristics. Based on the analysis of role preferences in repertoire lattices and the distribution of the real self and the ideal self by type of communication, the levels of stability of the self-concept and the basic characteristics of a speech act are described, such as the nature of one’s own message, the correspondence of what is communicated and what is experienced, one’s position and role in communication, type of speech behavior, giving another person a role in communication. Theoretical significance – a tool is proposed for determining the level of stability of the self-concept, which, in unity with the type of communication, influences the nature of the speech act of a first-year student. Practical significance – determining the individual characteristics of a speech act will allow us to identify the level of formation of self-awareness of the subject of cognition, which will contribute to the creation of psychological and pedagogical conditions aimed at identifying the adaptive potential of first-year students at the initial stage of professionalization (initiation).